Customer Acquisition Strategies of Be in Vietnam’s Ride-Hailing Industry - Nguyen, Thi Minh Phuong; Vaculová, Barbora; Koudelka, Jan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
The proposed study was planned for the purpose of examining the effectiveness of three unique and outstanding marketing campaigns of Be Group, a ride-hailing business primarily operating in the Vietnamese market, in its customer acquisition goal. In order to be able to meet the research’s objectives, it is essential to get a comprehensive understanding of the influence of Be’s CET brand positioning, penetration pricing, and salience marketing campaigns on customers’ decisions. This leads to the use of qualitative research due to its ability to explore and obtain the customers’ perspective about the objects being studied. And the in-depth interview, a supportive tool of qualitative research, was about to be used with the participation of 11 young Vietnamese individuals aged 20 - 28 who are considered the brand’s target customers. After the interviews were conducted, the collected information would be analyzed and interpreted, followed by a thematic approach. The current research results illustrate that, besides the penetration pricing playing the main role in acquiring customers for Be, a pure Vietnamese brand, salience campaigns (Be boat, Be hair-washed, etc.) also affect the customer decision to a specific extent. The study findings help the brand look back on the effectiveness of its past marketing activities and identify the omissions for better marketing plans. A key limitation of the study is the limitation in the number of respondents and the timing, which reduces the depth of findings.
Vedoucí práce: Barbora Vaculová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses